Hippocampus and amygdalar volumes in patients with somatization disorder - Atmaca, Murad; Sirlier, Burcu; Yildirim, Hanefi; Kayali, Alperen (Pergamon-Elsevier Science Ltd, 2011)
In regard to somatization disorder which covers an important section of our patient population, there is no systematic structural magnetic resonance imaging (MRI) study in the literature. Therefore, we aimed to use structural MRI to evaluate the hippocampus amygdalar complex which is associated with both stress and regulation of emotion that are main basis clinical presentation of somatization disorder in the patients with somatization disorder. Totally 40 subjects (20 patients with somatization disorder and 20 healthy controls) were enrolled. Intracranial volume (ICV), whole brain volume, gray and white matter volumes, and hippocampus and amygdalar volumes of the subjects were measured. In regard to unadjusted mean volumes of measured structures, the patients had significantly smaller mean volumes of the left and right amygdala. However, two groups did not differ significantly in terms of whole brain, total gray and white matter or hippocampus volumes. The repeated measures ANCOVA predicting left and right amygdala volumes demonstrated a significant main effect of diagnostic group. In conclusion, the findings of the present study revealed that the patients with somatization disorder had significantly smaller mean volumes of the left and right amygdala without any differences in regard to whole brain, total gray and white matter or hippocampus volumes. On the basis of the current findings, it seems reasonable to evaluate that abnormalities in connectivity and/or metabolism dimensions and to examine the effects of drugs or psychotherapeutic approaches could be especially informative. (C) 2011 Published by Elsevier Inc.
Keywords: Amygdala; Hippocampus; MRI; Somatization disorder; Volume